Jackfruit Seed Based Activated Carbon Prepared By Microwave Heating Activation For Methylene Blue Dye Removal - James Gunam, Joanna Jayamalar (Universiti Sains Malaysia, 2018)
A batch study was used to investigate the adsorption of methylene blue (MB) dye onto jackfruit seed based activated carbon (JSAC). Jackfruit seed goes through physical adsorption alongside with microwave heating and carbon dioxide (CO2) gasification. By using response surface methodology (RSM), the optimum preparation conditions were obtained with microwave power and activation time of 616W W and 6.00 minutes, respectively which resulted 83.15% MB removal. The effect of initial dye concentration (25-300 mg/L), contact time (0-24 hours) and solution temperature (30-60⁰C) were also evaluated throughout. This optimized sample has high surface area 544.07 m2/g, pore volume 0.3034 cm3/g and fixed carbon content of 75.22%. The pore of JSAC was mesoporous type with average pore diameter of 2.23 nm. The effect of initial dye concentration (25-300 mg/L), contact time (0-24 hours) and solution temperature (30-60⁰C) were also during this study. The obtained equilibrium data for MB adsorption by JSAC dye was best fitted by Langmuir model with monolayer adsorption capacity of 357.14 mg/g. Meanwhile, the kinetics data was best represented by the pseudo first-order model. The adsorption process of MB onto JSAC was endothermic which occurs spontaneous process.